SUN-LB112 Efficacy & Safety After Switchover to Remogliflozin in Indian T2DM Patients - a Real World Study - Bhattacharyya, Supratik (J Endocr Soc, 2020)
INTRODUCTON: Remogliflozin is new SGLT2i recently approved in India, but more economical than the previously available SGLT2i. It is prudent to evaluate its effectiveness & tolerability in comparison to other SGLT2i in real world setting. METHODS: In this observational retrospective study, medical data from EMR of tertiary care hospital in Kolkata was retrieved. The records of adult Type 2 diabetes mellitus (T2DM) patients who were on a dual therapy of Metformin plus SGLT2i (Canagliflozin, Dapagliflozin or Empagliflozin) for at least 6 months with adequate glycaemic control (HbA1c to target based on age & duration of diabetes) & subsequently switched over to Remogliflozin 100 mg twice daily because of economic reasons were screened. The day of switchover was considered as index day (Day 1) The patient records whose data was unavailable, metformin dose was altered during period of next 6 months, who had evidence of active UTI on index day, were receiving injectable anti-diabetic drugs or had recorded eGFR <45 mL/min were excluded. The effectiveness was assessed in terms of maintenance of HbA1c, FBS, PPBS, body weight after 3 & 6 months of treatment. The safety was assessed by adverse events recorded in medical records in terms of abnormal symptoms, signs or laboratory reported values during the observation period of 6 months & compared to equivalent period of 6 months before index day. The data was collected & analysed using appropriate statistical techniques. RESULTS: After screening, medical records of 50 adult T2DM patients (54% male) were found to be eligible. The mean baseline characteristics on Index day in terms of Age, HbA1c levels, FBS, PPBS, weight & BMI was 51.3±12.5 years, 6.8±0.4%, 108.7±8.1 mg/dL, 144.5±21.3 mg/dL, 65.5±5.7 kg & 25.8±2.8 kg/m2 respectively. After treatment period of 6-months with Remogliflozin-based regimen, the mean HbA1c, FBS, PPBS, -Body weight & BMI was 6.7±0.8%, 110.3±10.5 mg/dL, 138.5±12.7 mg/dL, 66.3±6.5 kg & 25.9±3.2 kg/m2 Mean change from baseline in HbA1c levels, FBS, PPBS, weight & BMI were-0.1±0.19%, -1.6±7.2 mg, -6.0±8.3 mg, +0.8±0.2kg, & +0.1±0.0.7 kg/m2 respectively. These change from baseline of all above parameters were not found to be statistically significant (P>0.05) No events of hypoglycaemia, disturbance in electrolytes or any unusual adverse events were reported. Combined incidence of UTI & genital Mycotic infection was similar during 6 month observation period as compared to 6 months prior to index day. (8% vs 6%) CONCLUSION: In real world clinical practice, replacement of ongoing SGLT2i with Remogliflozin was observed to provide consistent glycaemic control without any tolerability issues. Hence, novel SGLT2i Remogliflozin can be considered as equivalent alternative for SGLT2i based regimen in management of Indian T2DM patients